Menuju Kristologi Transeklesial: Bergerak Melampaui Kristologi Transdenominasional Roger Haight - Pattipeilohy, Stella Yessy Exlentya; Simon, John Christianto (Sekolah Tinggi Teologi SAAT (Southeast Asia Bible Seminary), 2024)
This paper seeks a model of Christology that is non-anthropocentric and relevant in the current context. Roger Haight is chosen because he has a distinct way of etransecclesialsignificance of Jesus’ work of God's salvation through its relation to postmodern experiences that are interfaith and cross-cultural—hence, a “transdenominational Christology.” In line with his Christology, Haight’s ecclesiology project can also called “transdenominational ecclesiology,” which is an appreciative ecclesiological picture of what enlivens and moves, of a common framework and language for ecumenical dialogue, interaction with society and the world, and interfaith dialogue. Such a transdenominational Christology and ecclesiology encourages the Church to discover the presence of Christ in the particular context and realize its universality, and brings out the value of the public witness of the Church. From here, the author moves beyond Haight and develops a transecclesial Christology that becomes the basis for the Church to move, share, borrow, and theologize contextually, specifically in the context of relations with other religions, poverty, oppression, suffering, and ecological destruction.